Tectonic control and mass-wasting processes along S. Vicente Canyon (SW Iberia) : evidences from multibeam bathymetry and seismic reflection data - Valadares, Vasco (2015)
European Geosciences Union General Assembly 2009 (EGU 2009), Vienna, Austria, April 19-24, 2009